Analysis of Integrated Marketing Communication Strategy for Surabaya Medical Tourism - Junaedi, Rusli Akhmad (P3M Politeknik Negeri Jember, 2024)
This article investigates an integrated marketing communication (IMC) strategy to develop Surabaya Medical Tourism's marketing process so that local medical tourists know Surabaya City's identity as a medical tourism destination. Background draws its inspiration from the fact that many residents of Surabaya City opt to seek medical treatment abroad despite Surabaya City being a popular destination for medical tourism and home to several major hospitals in Indonesia. The method uses a case study design with a qualitative methodology. Collected data through in-depth interviews, observations, and document analyses. This goal is achieved by applying data triangulation. The results show that IMC strategies consist of two main activities in the pre-trip stage. Digital marketing activities involve endorsement by optimizing owned media with paid programmatic advertising. Enhance event and experience activities by leveraging MICE collaboration and community marketing strategies. IMC strategies on stage during the trip include content marketing with informative content and a special bundling package. IMC strategies in the after-trip stage include referral marketing, electronic word-of-mouth communications, and feedback optimization.